2007
DOI: 10.1016/j.jinorgbio.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the CO-sensing heme protein CooA: New insights from the truncated heme domain and UVRR spectroscopy

Abstract: The bacterial CO-sensing heme protein CooA activates expression of genes whose products perform CO-metabolism by binding its target DNA in response to CO binding. The required conformational change has been proposed to result from CO-induced displacement of the heme and of the adjacent C-helix, which connects the sensory and DNA-binding domains. Support for this proposal comes from UV Resonance Raman (UVRR) spectroscopy, which reveals a more hydrophobic environment for the C-helix residue Trp110 when CO binds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Therefore, it is suggested that DNA binding or truncation of the DNA-binding domain leads to a reduction in the volume of the distal pocket. This view agrees with UV resonance Raman results that monitor the vibrational modes associated with Trp-110 in the C-helix (13,14). Comparison of the Trp-110 bands of the inactive ferrous RrCooA with those of RrCooACO shows that these bands are enhanced upon CO binding (13,14).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it is suggested that DNA binding or truncation of the DNA-binding domain leads to a reduction in the volume of the distal pocket. This view agrees with UV resonance Raman results that monitor the vibrational modes associated with Trp-110 in the C-helix (13,14). Comparison of the Trp-110 bands of the inactive ferrous RrCooA with those of RrCooACO shows that these bands are enhanced upon CO binding (13,14).…”
Section: Discussionsupporting
confidence: 86%
“…1C). In this structure, one of the monomers is without its heme, but the other one contains a CO-bound heme and shows heme sliding and C-helix displacement similar to those predicted by resonance Raman and UV resonance Raman studies (11)(12)(13)(14). The structure also shows an unexpected movement of the N-terminal region, displaced by CO, so that it is repositioned between the heme and the DNA-binding domains.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…S1). CooA resembles Escherichia coli CRP in structure, but reorientation of CooA DNA-binding domains is needed to produce a transcriptionally active state (61). CO binding may accompany a shift in heme position to a hydrophobic cavity and movement of the C-helix of CooA toward the opposite heme to restructure the CO-binding pocket.…”
Section: Cooamentioning
confidence: 99%
“…CO binding may accompany a shift in heme position to a hydrophobic cavity and movement of the C-helix of CooA toward the opposite heme to restructure the CO-binding pocket. This switch reorganizes a hinge between the C-and D-helices to enable DNA-binding domains to interact with DNA (61 2 ] ranges in which it triggers target gene transcription (68). The five-coordinate (deoxy) FixL is "active" and directs induction of genes encoding high O 2 affinity terminal oxidases for microaerobic respiration (the likely main role of FixL in non-N 2 -fixing bacteria/archaea) and for nitrogenase subunits (S. meliloti) or denitrification enzymes (B. japonicum) (67).…”
Section: Cooamentioning
confidence: 99%